Romania and the EU’s Common Foreign and Security Policy - Daniel Călin (Romanian Journal of European Affairs, 2003)
Within this article, the author tries to sum up the most salient steps undertaken by Romania on the way to the EU, with respect to an area of particular importance for the Union, i.e. CFSP. After a presentation on its actions in CFSP area, one reviews in short the stances adopted by Romania vis-à-vis the new child of EU policies, i.e. ESDP, as well as towards the Romanian involvement / participation in military crisis management. In the end, the European security policy and the enlargement of both the EU and NATO are assessed in the light of the coming IGC and against the background of the 9/11 events.